A new species of Platybaetis Müller-Liebenau, 1980 (Ephemeroptera: Baetidae) from Thailand, with description of the imago of Platybaetis bishopi Müller-Liebenau, 1980 - Sutthinun, Chanaporn; Gattolliat, Jean-Luc; Boonsoong, Boonsatien (Zootaxa, 2018)
Platybaetis bishopi Müller-Liebenau, 1980 was originally described from Malaysia only at the larval stage. We provide the first description of the imaginal stage of P. bishopi based on materials from Thailand. The imago of this species can be separated from the known species by coloration of abdominal terga and coloration of wings. A new species, Platybaetis nayokensis sp. nov., is described based on male and female imagos and larvae from Thailand. The larva of this species is mainly distinguished by medium acute spines on the posterior margin of the abdominal terga and two apical setae on the glossa, which seem to be shorter than in other species. The imago can be separated by the abdominal color pattern. The larva of this genus is adapted to live on wet rocks projecting out of water; it prefers large stones near small waterfalls or areas between two large rocks in running water.